Studi Kasus Motivasi Mahasiswa Pendidikan Ekonomi FKIP UMMY Solok dalam Menyelesaikan Skripsi - Ariani, Dewi; Jesni, Resi Putri (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
The aim of this research is to analyze 1) Motivation of students in finishing thesis, 2) Lecturer responces to student's motivation in finishing thesis, 3) Factors that influence student's motivation in finishing thesis. This research is qualitative research. The key informant are the students and lecturer of Economics Education. The interview given to the informant by using sampling insidental technique. The result of this research are: 1) Which where students had been doing thesis, consul, read a lot refences, however there are some students of Economics Education yet show their seriously in finishing thesis 2) Lecturer responces include to student’s motivation in finishing thesis are getting better, its shows from the students meet the lecturer to get thesis consul. However, still some students who not yet meet their academic consul at all, 3) There are two factors that effect students motivation. Intrinsic factor, such as student's motivation to invest in yourself, keep motivation from that desiring or eager to work on thesis. But students difficulties of keeping the motive for in herself when many obtacles in face in the resolution of thesis as for reference books, process data after research make students lazy to do so that the motive for thesis in those accessible well. While external factor, motivation students easily get encouragement and enthusiasm from various parties. For that, researcher suggest the students to increase their motivation in doing the research and following the rules by the advisors in order to gradute on time.